2003
DOI: 10.1017/s0016774600020680
|View full text |Cite
|
Sign up to set email alerts
|

Relative water-level rise in the Flevo lagoon (The Netherlands), 5300-2000 cal. yr BC: an evaluation of new and existing basal peat time-depth data

Abstract: The rise of Holocene (ground)water level as a function of relative sea-level rise has been extensively investigated in the western Netherlands, whereas few studies focused on the Flevo lagoon in the central Netherlands. In this study, all available ,4 C dates from the base of basal peat overlying the top of compaction-free Pleistocene sand in the former Flevo lagoon were evaluated in order to reconstruct water-level rise for the period 5300-2000 cal. yr BC. The present basal peat 14 C data set from Flevoland c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…In a discussion of the available water-level evidence from Flevoland, Makaske et al (2003) proposed three hypothetical explanations for the difference between the Flevoland data and the MSL curve of Van de Plassche (1982): (1) the latter curve erroneously indicates a water level higher than MSL, (2) relative basin subsidence has caused lowering of the Flevoland data relative to the MSL curve, (3) the Schokland data (Roeleveld & Gotjé, 1993) are unreliable. Hypothesis 3 has been ruled out by the research of Van de Plassche et al (2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a discussion of the available water-level evidence from Flevoland, Makaske et al (2003) proposed three hypothetical explanations for the difference between the Flevoland data and the MSL curve of Van de Plassche (1982): (1) the latter curve erroneously indicates a water level higher than MSL, (2) relative basin subsidence has caused lowering of the Flevoland data relative to the MSL curve, (3) the Schokland data (Roeleveld & Gotjé, 1993) are unreliable. Hypothesis 3 has been ruled out by the research of Van de Plassche et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of summing vertical errors and uncertainties to obtain a maximum vertical range, as has been done in previous palaeowater-level studies (e.g., Törnqvist et al, 1998;Makaske et al, 2003;Van de Plassche et al, 2005), we calculated a total vertical standard deviation based on the various vertical errors and uncertainties mentioned above (except the 'oneway upward corrections' 3b and 4) that are considered as estimates of the 2σ error range (Table 1; a table containing the details of the calculations can be downloaded from: http://www.geo.uu.nl/fg/palaeogeography). Although this total vertical standard deviation necessarily is based on estimates, this statistical approach is more consistent with the way age-error margins (see below) are represented.…”
Section: Depth-error Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…From recently published paleowater-level data we infer that relative average water level in the Flevo area was below the 1982-MSL curve at least as far back as 5300 cal BC. Makaske et al (2002Makaske et al ( , 2003 found that the age-depth position of five new, reliable basal peat samples collected ca. 50 km southwest of Schokland (near the town of Almere; sites d and e in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our objective is to test the hypothesis that the younger part of the Schokland curve runs below the 1982-MSL curve because (1) the radiocarbon ages of the bulk-dated peat samples obtained by RG93 are too ARTICLE IN PRESS (Fig. 1b) where water-level index data were collected, b: Engwierumer polder (Griede, 1978), c: near Rotterdam ( Van de Plassche, 1982), d: and e: near Almere (Makaske et al, 2003); (b) eastern Flevo area, 4: Urk (Roeleveld and Gotje´, 1993), a: Swifterbant (Ente et al, 1986); and (c) former island of Schokland with main study sites (1, 2 and 3) of Roeleveld and Gotje´(1993). For the present paper we revisited site 1.…”
Section: Introductionmentioning
confidence: 99%